Energy consumption models in VANET simulation tools for electric vehicles: a literature survey. (7th December 2022) - Sagaama, Insaf; Kchiche, Amine; Trojet, Wassim; Kamoun, Farouk
Electric vehicles (EVs) have been widely recognised as a key technology of the intelligent transportation systems (ITSs) to make both public and private transportation services more economic and ecological. The energy-saving in the case of EVs is a viable solution to promote smart navigation and extending the driving range. Realistic traffic simulations contribute to the large-scale diffusion of EVs in the future market. In particular, vehicular ad hoc networks (VANETs) simulation tools integrate often an energy model for calculating the vehicle energy consumption. Hence, the EVs raise a new challenge about integrating reliable and accurate energy models in the traffic simulators for this category of vehicles. In this paper, we present a thorough study about energy models elaborated in the automotive sector to provide valuable enhancements to VANET simulators. The main goal is to establish an accurate estimation of the EV consumption and recuperation in VANET simulation tools.